Business cycles: A role for imperfect competition in the banking system - Federico S. Mandelman (Federal Reserve Bank of Atlanta, 2006)
This paper studies the cyclical pattern of ex post markups in the banking system using balance-sheet data for a large set of countries. Markups are strongly countercyclical even after controlling for financial development, banking concentration, operational costs, inflation, and simultaneity or reverse causation. The countercyclical pattern is explained by the procyclical entry of foreign banks, which occurs mostly at the wholesale level and signals the intention to spread to the retail level. My hypothesis is that wholesale entry triggers incumbents' limit-pricing strategies, which are aimed at deterring entry into retail niches and which, in turn, dampen bank markups. In the second part of the paper, I develop a general equilibrium model that accounts for these features of the data. I find that this monopolistic behavior in the intermediary financial sector increases the volatility of real variables and amplifies the business cycle. I interpret this bank-supply channel as an extension of the credit channel pioneered by Bernanke and Blinder (1988).
Keywords: C23; E32; G21; L12; O16; 330; countercyclical bank markups; limit pricing; business cycles; panel data; generalized method of moments; Konjunktur; Kreditmarkt; Antizyklisches Verhalten; Bankensystem; Unvollkommener Wettbewerb; Makroökonomischer Einfluss; Dynamisches Gleichgewicht; Neukeynesianische Makroökonomik; Theorie; Welt